Hockey : a global history - Hardy, Stephen, 1948-; Holman, Andrew C. (Andrew Carl), 1965- (Sport and society., 2018)
"Until the 1990s, the bulk of hockey history was focused on the National Hockey League and its celebrities, was written by Canadians for Canadians, and was not scholarly in either research methods or presentation. That has begun to change, but only slightly, as evidenced in the slew of breezy, triumphant books published this year as the NHL celebrates its centennial. Based on 25 years of research, this book re-centers hockey's story toward a North Atlantic panorama that unfolded over the last two centuries amid currents of global capitalism. Rather than assume the domination of one Canadian version of hockey, this project traces the history of convergence, divergence and reconvergence of a range of hockeys, via stories of people, organizations, venues, contests, equipment, coaching strategies, marketing schemes, and political campaigns. The story is organized around dates that emerged from primary sources on hockey: 1875, when a new version of the game appeared in Montreal and began to move with the broadening currents of global capitalism; 1920, when the Montreal version became THE Olympic version, both solidifying its international position and spawning separate brands that spoke to nationalist aspirations arising--especially in Europe--as global capitalism collapsed during world wars, a depression, and a cold war; 1972, when a Soviet-NHL Summit Series triggered a new era when national differences slowly evaporated in favor of an NHL-centered industry we call "corporate hockey," which grew amid global capitalism's return. In The Coolest Game, hockey is not just a mirror of developing economic-political-cultural systems. Instead, it is an active ingredient in making those systems"--